Epidural Volume of Injectate Using a Dose Regimen Based on Occipito-Coccygeal Spinal Length (OCL): Randomized Clinical Study Comparing Different Ropivacaine Concentrations, with or without Morphine, in Bitches Undergoing Total Unilateral Mastectomy - Hamaseh Tayari; Pablo E. Otero; Marco D’Agostino; Flavia Bartolini; Angela Briganti (Animals, 2022)
A prospective, randomized clinical trial was designed to compare four epidural treatments in dogs undergoing total unilateral mastectomy. The epidural volume of injectate was based on the individual occipito-coccygeal length (OCL) aiming to reach the first thoracic vertebra (T1). The first ten dogs were allocated in a control group (C) and did not receive epidural treatment. Subsequently, forty dogs were randomly allocated in four groups of ten: epidural ropivacaine 0.5% (R0.5%); morphine 0.1 mg kg−1 plus ropivacaine 0.5% (MR0.5%); morphine 0.1 mg kg−1 plus ropivacaine 0.35% (MR0.35%); morphine 0.1 mg kg−1 plus ropivacaine 0.25% (MR0.25%). Intraoperatively, isoflurane requirement (1.3% vs. <1.1% FE’Iso) and fentanyl requirement (9.8 vs. <1.1 µg kg−1 h−1) were significantly higher in C group compared to all epidural groups. Postoperatively, methadone requirement was higher (1.8 mg kg−1 vs. <0.8 mg kg−1) for C group compared to all epidural treatment groups. The ability to walk and to urinate returned 4 h earlier in MR0.35% and MR0.25%. The mean epidural volume of ropivacaine, using a dose regimen based on OCL, to reach T1 was about 0.15 mL cm−1. The addition of morphine further reduced the methadone requirement, without affecting urinary and motor functions.